Acylindrical Hyperbolicity of Out(W_n) - Healy, Brendan Burns (Topology Proceedings, 2020)
We prove that the group of outer automorphisms of the free Coxeter group W_n is acylindrically hyperbolic in the sense of Osin. We observe that any CAT(0) space admitting a geometric action by Out(W_n) must contain a rank-one geodesic as an application. Our main theorem proceeds from expanding on a well-known relationship between Out(W_n) and the outer automorphism group of free groups.